2014
DOI: 10.1177/147470491401200103
|View full text |Cite
|
Sign up to set email alerts
|

Current Hormonal Contraceptive Use Predicts Female Extra-Pair and Dyadic Sexual Behavior: Evidence Based on Czech National Survey Data

Abstract: Data from 1155 Czech women (493 using oral contraception, 662 non-users), obtained from the Czech National Survey of Sexual Behavior, were used to investigate evolutionary-based hypotheses concerning the predictive value of current oral contraceptive (OC) use on extra-pair and dyadic (in-pair) sexual behavior of coupled women. Specifically, the aim was to determine whether current OC use was associated with lower extra-pair and higher in-pair sexual interest and behavior, because OC use suppresses cyclical shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The fact that the model was not significant when pooling all methods of birth control to predict relationship satisfaction may support increased confidence in the interpretation that OCs, specifically, may stabilize women's mood, which in turn may have beneficial consequences in other areas of women's lives. Other possible reasons that might explain or contribute to this association include other effects from OCs such as decreased extrapair sexual desire and activity, more frequent intercourse with their partners (Klapilová et al, 2014), and longer relationships despite experiencing decreased rates of sexual satisfaction with and attraction to their partners (Roberts et al, 2011;Roberts et al, 2014), starting or stopping OCs during a relationship because it has been shown to affect relationship outcome (Roberts et al, 2011), rates of relationship satisfac tion before beginning birth control and how they change over time, the impact of their partner's mental health, and the ease of using OCs over other forms of birth control. As such, these find ings were merely correlational and should not be interpreted as causal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the model was not significant when pooling all methods of birth control to predict relationship satisfaction may support increased confidence in the interpretation that OCs, specifically, may stabilize women's mood, which in turn may have beneficial consequences in other areas of women's lives. Other possible reasons that might explain or contribute to this association include other effects from OCs such as decreased extrapair sexual desire and activity, more frequent intercourse with their partners (Klapilová et al, 2014), and longer relationships despite experiencing decreased rates of sexual satisfaction with and attraction to their partners (Roberts et al, 2011;Roberts et al, 2014), starting or stopping OCs during a relationship because it has been shown to affect relationship outcome (Roberts et al, 2011), rates of relationship satisfac tion before beginning birth control and how they change over time, the impact of their partner's mental health, and the ease of using OCs over other forms of birth control. As such, these find ings were merely correlational and should not be interpreted as causal.…”
Section: Discussionmentioning
confidence: 99%
“…OCs have been shown to alter the sexual behavior of coupled women, which may also account for the impact to their relation ships and interpersonal functioning. In one study, women who used OCs had fewer extrapair affairs and more frequent intercourse with their partners than nonusers, which may suggest higher levels of commitment to the relationship (Klapilová et al, 2014). It is important to note that this information does not imply that women are solely responsible for the satisfaction of their partners.…”
Section: Oral Contraceptive Use Associated With Increased Romantic Relationship Satisfactionmentioning
confidence: 99%